Genome-wide association study of survival in patients with pancreatic adenocarcinoma. Issue 1 (24th November 2012) - Wu, Chen; Kraft, Peter; Stolzenberg-Solomon, Rachael; Steplowski, Emily; Brotzman, Michelle; Xu, Mousheng; Mudgal, Poorva; Amundadottir, Laufey; Arslan, Alan A; Bueno-de-Mesquita, H Bas; Gross, Myron; Helzlsouer, Kathy; et al.
Abstract : Background and objective: Survival of patients with pancreatic adenocarcinoma is limited and few prognostic factors are known. We conducted a two-stage genome-wide association study (GWAS) to identify germline variants associated with survival in patients with pancreatic adenocarcinoma. Methods: We analysed overall survival in relation to single nucleotide polymorphisms (SNPs) among 1005 patients from two large GWAS datasets, PanScan I and ChinaPC. Cox proportional hazards regression was used in an additive genetic model with adjustment for age, sex, clinical stage and the top four principal components of population stratification. The first stage included 642 cases of European ancestry (PanScan), from which the top SNPs (p≤10 −5 ) were advanced to a joint analysis with 363 additional patients from China (ChinaPC). Results: In the first stage of cases of European descent, the top-ranked loci were at chromosomes 11p15.4, 18p11.21 and 1p36.13, tagged by rs12362504 (p=1.63×10 −7 ), rs981621 (p=1.65×10 −7 ) and rs16861827 (p=3.75×10 −7 ), respectively. 131 SNPs with p≤10 −5 were advanced to a joint analysis with cases from the ChinaPC study. In the joint analysis, the top-ranked SNP was rs10500715 (minor allele frequency, 0.37; p=1.72×10 −7 ) on chromosome 11p15.4, which is intronic to the SET binding factor 2 (SBF2) gene. The HR (95% CI) for death was 0.74 (0.66 to 0.84) in PanScan I, 0.79 (0.65 to 0.97) in ChinaPC and 0.76 (0.68 to 0.84) in the joint analysis. Conclusions: Germline genetic variation in the SBF2 locus was associated with overall survival in patients with pancreatic adenocarcinoma of European and Asian ancestry. This association should be investigated in additional large patient cohorts.